2017
DOI: 10.5395/rde.2017.42.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Color stability of bulk-fill and incremental-fill resin-based composites polished with aluminum-oxide impregnated disks

Abstract: ObjectivesThis study aimed to evaluate the color stability of bulk-fill and nanohybrid resin-based composites polished with 3 different, multistep, aluminum-oxide impregnated finishing and polishing disks.Materials and MethodsDisk-shaped specimens (8 mm in diameter and 4 mm in thickness) were light-cured between two glass slabs using one nanohybid bulk-fill (Tetric EvoCeram, Ivoclar Vivadent), one micro-hybrid bulk-fill (Quixfil, Dentsply), and two nanohybrid incremental-fill (Filtek Ultimate, 3M ESPE; Herculi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…Coffee has a yellow colorant pigment that has different polarities and a strong affinity to polymers; these properties may be the reason for the color change of the composite resins . A recent study reported the effect of different polishing procedures on the color change of bulk fill composite resin against coffee . Authors reported clinically unacceptable color change after 7‐day storage in coffee for bulk‐fill composite resins except for 1 group, and this group was polished differently.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Coffee has a yellow colorant pigment that has different polarities and a strong affinity to polymers; these properties may be the reason for the color change of the composite resins . A recent study reported the effect of different polishing procedures on the color change of bulk fill composite resin against coffee . Authors reported clinically unacceptable color change after 7‐day storage in coffee for bulk‐fill composite resins except for 1 group, and this group was polished differently.…”
Section: Discussionmentioning
confidence: 99%
“…11,28 A recent study reported the effect of different polishing procedures on the color change of bulk fill composite resin against coffee. 9 Authors reported clinically unacceptable color change after 7-day storage in coffee for bulk-fill composite resins except for 1 group, and this group was polished differently. It was reported that the color stability of bulk-fill composite resins in this study was polishing technique-dependent.…”
Section: Re S U Lt Smentioning
confidence: 99%
See 2 more Smart Citations
“…An exception is a fiber‐reinforced bulk‐fill composite everX Posterior (GC) requiring a final layer of another composite due to its long glass fibers. Differences in color stability between bulk‐fill and universal composites were found in staining media, albeit with inconclusive data, depending on composite brands, layer thickness, polishing procedures, and staining media …”
Section: Introductionmentioning
confidence: 99%